PENERAPAN PENDEKATAN INQUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 013 BASILAM BARU DUMAI - Istiqomah '; Munjiatun ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstraction: This Research of Action class(CAR) is class of V SDN 013 Basilam Baru semester of II school year 2013 / 2014 with amount of student 10 people by 3 joe and 7 women. This research use two cycle. First cycle twice meeting with one daily restating. Second Cycle twice finding with one daily restating. This research by teacher and learn class of IV. Variable in this research is free variable ( variable and independent) do not be free ( dependent). Free variable is applying of approach of Inkuiri and variable tied of  result learn IPA student. Data early this  obtaining from anomalous semester value class of V SDN 013 Basilam Baru. Research the used research of class action. Research to overcome the problem of faced in course of study. This research expecting the make-up of in study. Data early the used to determine group learn which formed have the character of heterogeneously, each;every group consist of ability of different gender and akademik  average elementary score that is 68,8. UH I student average mount to become 75,5. UH II student average mount to become 8,1. Complete percentage  klasikal cycle of I 70%, and cycle of II 90%. Action hypothesis which have theoretical study accepting. Equally applying of approach of inkuiri can improve result learn IPA class student Key word. Leraning Models of Inkuiri, Outcomes learning IPA